Estimating the number of female sex workers in Côte d'Ivoire: results and lessons learned. Issue 9 (5th July 2017) - Vuylsteke, Bea; Sika, Lazare; Semdé, Gisèle; Anoma, Camille; Kacou, Elise; Laga, Marie
Abstract: Objective: To report on the results of three size estimations of the populations of female sex workers (FSW) in five cities in Côte d'Ivoire and on operational lessons learned, which may be relevant for key population programmes in other parts of the world. Methods: We applied three methods: mapping and census, capture–recapture and service multiplier. All were applied between 2008 and 2009 in Abidjan, San Pedro, Bouaké, Yamoussoukro and Abengourou. Results: Abidjan was the city with the highest number of FSW by far, with estimations between 7880 (census) and 13 714 (service multiplier). The estimations in San Pedro, Bouaké and Yamoussoukro were very similar, with figures ranging from 1160 (Yamoussoukro, census) to 1916 (San Pedro, capture–recapture). Important operational lessons were learned, including strategies for mapping, the importance of involving peer sex workers for implementing the capture–recapture and the identification of the right question for the multiplier method. Conclusions: Successful application of three methods to estimate the population size of FSW in five cities in Côte d'Ivoire enabled us to make recommendations for size estimations of key population in low‐income countries.